Karakteristik Bubur Instan Berbasis Ubi Jalar Kuning dan Tempe - Yanti, Novita; Shanti, Fitriani; Efendi, Raswen (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 2 (2022)DO - 10.24843/JITPA.2022.v07.i02.p07, 2022)
Instant porridge is a practical food processed product that is easy for people to consume and has a soft texture and easy to digest.  The purpose of this research was to get the best formulation of yellow sweet potato and tempeh on the chemistry characteristics and sensory characteristics of instant porridge.  The research method used a completely randomized design with five treatments and three replications.  The treatments used yellow sweet potato and tempeh with variation treatment: JT1 (yellow sweet potato and tempeh 90:1), JT2 (yellow sweet potato and tempeh 80:20), JT3 (yellow sweet potato and tempeh 70:30), JT4 (yellow sweet potato and tempeh 60:40), and JT5 (yellow sweet potato and tempeh 50:50).  The data obtained were statistically analyzed using analysis of variance and continued with Duncan's Multiple Range Test (DMRT) at the 5% level.  The results showed that the combination of yellow sweet potato and tempeh significantly affected moisture, ash, fat, protein and carbohydrate content.  Based on the result of this research, the combination of yellow sweet potato and tempeh 90:10 was chosen as the best treatments: moisture content 7.79%, ash content 4.66%, fat content 3.28%, protein content 8.97% and carbohydrate content 76.68%.